Frequency of carrier state of thalassemia and various hemoglobinopathies in tertiary care hospital of Pakistan. - Kamil, Saba; Shaheen Kousar; Rafique , Sara; Qadri, Hira; Farooqui, Waqas; Moazzam Tauheed; Kamil, Noor; Anum Liaquat (International Journal of Endorsing Health Science Research, 2021)
Background: It has been estimated that 5% of the global population are carriers of Hemoglobin (Hb) disorders. These disorders may cause hemolytic anemia leading to the critical condition of the patients. The current research was designed to identify spectrums of thalassemia minor and carriers of other hemoglobinopathies patients presenting at the tertiary care center to evaluate anemia. Methodology: A total of 3289 patients’ data with low Hb values and suspicion of hemoglobinopathies were included in this cross-sectional retrospective study. Complete blood count (CBC), High-performance liquid chromatography (HPLC), and sickling test were utilized in this study. At the same time, Patients with normal Hb as per HPLC analysis were excluded from this study. Results: Of the total, 708 (21.5%) patients had hemoglobin disorder and the mean age of patients with thalassemia minor was 24.0 ± 14.7 years. Out of 708 carriers, 646 (19.6%) cases showed traits of thalassemia minor, 12 (0.36%) showed Hb S trait, 43 (1.30%) showed Hb D trait, 07 (0.21%) showed Hb E trait, whereas there were no cases of Hb C recorded in this study. Conclusion: Thalassemia trait was the highest among other variants in our study population. It is recommended that to decrease the frequency of hemoglobinopathies, pre-marriage screening should be conducted, and family marriages should be restricted.